2017
DOI: 10.5194/bg-2017-444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbon dynamics in the Mekong Delta

Abstract: We report a data-set obtained in the three branches (My Tho . The CO 2 emission to the atmosphere from the Mekong inner estuary was higher than reported in the Yangtze and Pearl River inner estuaries. This was probably due to the lower salinity in the Mekong delta branches, possibly due to different morphology; relatively linear channels in the Mekong delta versus funnel-15 shaped estuaries for the Yangtze and Pearl River inner estuaries.,Biogeosciences Discuss., https://doi

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 65 publications
3
12
1
Order By: Relevance
“…Lower GHG concentrations during the monsoon period (Figure 3) might have resulted from wastewater dilution by a monsoonal increase in discharge. However, higher concentrations of GHGs observed in several sites along the middle and lower reaches of the studied rivers (Figures 4, and ) are consistent with the patterns of pCO 2 observed in some sites of the lower Mekong (Borges, Abril, & Bouillon, 2018; Li et al., 2013) and the lower Yellow River (Ran et al., 2015). Monsoonal increases in CO 2 have been explained by the flushing of CO 2 and OM from the soil, floodplains, and other allochthonous sources and subsequent degradation of the allochthonous OM during riverine transport (Borges, Abril, & Bouillon, 2018; Li et al., 2013).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Lower GHG concentrations during the monsoon period (Figure 3) might have resulted from wastewater dilution by a monsoonal increase in discharge. However, higher concentrations of GHGs observed in several sites along the middle and lower reaches of the studied rivers (Figures 4, and ) are consistent with the patterns of pCO 2 observed in some sites of the lower Mekong (Borges, Abril, & Bouillon, 2018; Li et al., 2013) and the lower Yellow River (Ran et al., 2015). Monsoonal increases in CO 2 have been explained by the flushing of CO 2 and OM from the soil, floodplains, and other allochthonous sources and subsequent degradation of the allochthonous OM during riverine transport (Borges, Abril, & Bouillon, 2018; Li et al., 2013).…”
Section: Discussionsupporting
confidence: 86%
“…While δ 13 C has widely been measured to track downstream alterations of various DIC components in inland water systems, including CO 2 , HCO3, and CO32 (Borges, Abril, & Bouillon, 2018; Campeau et al., 2017; Jin et al., 2018), our approach is unique in linking the optical characterization of wastewater‐derived DOM to the isotopic signatures of CO 2 and CH 4 in the urbanized middle and lower reaches of the studied rivers. The measured values of δ 13 C‐CO 2 ranging from −6.0 to −24.5‰ (Table 2) span nearly the full range of reported values of δ 13 C‐CO 2 in streams, rivers, and estuaries (Campeau et al., 2017; Jin et al., 2018; Maher et al., 2013; McCallister & del Giorgio, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Alin et al (2011) measured similar values (~1200 atm) at eight mainstem locations in Laos and Cambodia. The seasonal trend in pCO2 opposes the alkalinity and DIC trends, peaking in the flood season and lowest in the dry season, similar to several previous studies in tropical river systems (Sarma et al, 2011;Borges et al, 2017). 420…”
Section: Effects Of Increasing Water Pollution In Asian River Systemssupporting
confidence: 70%
“…MoWRAM (2016) has recently reported that total nitrogen concentrations in the Mekong downstream the range of 703-1,597 atm observed in the upstream reach during the similar period (September-October, 2004 and2005) by Alin et al (2011). As suggested by Borges et al (2017), anthropogenic pollution sources in the densely populated and 435 cultivated areas of the Delta may release more CO2 and biodegradable OM compared to the upstream reach.…”
Section: Effects Of Increasing Water Pollution In Asian River Systemsmentioning
confidence: 97%
“…Rainfall and downstream dilution likely caused the exponential decline of DIC and TAlk with increasing river discharge (Figure ). Similar dilution effects of DIC and TAlk from rainfall or snowmelt have been found in the Chena (Amiotte Suchet, Probst, & Ludwig, ), the Mississippi (Cai, ; Raymond & Cole, ), the Changjiang (Cai et al, ; Zhai, Dai, & Guo, ), the Congo (Probst et al, ), the Pearl (Guo et al, ), and the Mekong rivers (Borges, Abril, & Bouillon, ). The lower slope of the power regression in the North and South Johnstone suggests that river flushing was more steadily and dilution more significant here compared to the other Great Barrier Reef rivers (Figure ).…”
Section: Discussionmentioning
confidence: 98%